1988
DOI: 10.1002/app.1988.070360508
|View full text |Cite
|
Sign up to set email alerts
|

The role of hindered piperidine (HALS) compounds for the stabilization of polypropylene against oxidation reactions caused by ozone and oxidative products formed during photolysis of ozone

Abstract: SynopsisThe role of hindered piperidine (HALS) photostabilizers for the photostabilization of polypropylene films against oxidative reactions caused by ozone and oxidative species formed during photolysis of ozone under UV irradiation (i.e., atomic oxygen and singlet oxygen) has been investigated and discussed. It has been found that ozonization and/or photoozonization of 2,2,6,6-tetramethyl-piperidine (I) and piperidinoxy radical (2,2,6,6-tetramethylpiperidino-l-oxy) (11) gives a high yield (91-988) 2,6-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…6 -8 Salts, more particularly salts of transition metals, act as catalysts in the auto oxidation of atactic PP. 9 -16 The oxidation of atactic PP may also be conducted in solvents such as monochlorobenzene or dichlorobenzene 12 at 70 -125°C, in the presence of ozone, 13,14 ditertiary butyl peroxalate, 15 or an aqueous solution 16 of K 2 Cr 2 O 7 /H 2 SO 4 . The oxidized PP (OPP) may be used as a compatibilizer in polymer blends; it may also be used as a lubricant or processing aid in certain alloys and composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…6 -8 Salts, more particularly salts of transition metals, act as catalysts in the auto oxidation of atactic PP. 9 -16 The oxidation of atactic PP may also be conducted in solvents such as monochlorobenzene or dichlorobenzene 12 at 70 -125°C, in the presence of ozone, 13,14 ditertiary butyl peroxalate, 15 or an aqueous solution 16 of K 2 Cr 2 O 7 /H 2 SO 4 . The oxidized PP (OPP) may be used as a compatibilizer in polymer blends; it may also be used as a lubricant or processing aid in certain alloys and composite systems.…”
Section: Introductionmentioning
confidence: 99%
“…This was not observed in the time frame of these experiments. Studies of the oxidation of polypropylene by ozone [17] indicated reaction times in the order hours are required for significant carbonyl and hydroxyl group formations. CONCLUSION It appears that the hollow fiber membrane reactor shows promise for transferring ozone.…”
Section: Mass Balance Analysismentioning
confidence: 99%
“…The slope (B) for the counter-current case is 1.5 times larger than for the co-current case. From the slope of each line, a mass transfer coefficient, ¿¿, can be derived by using equation (14) or (17). The calculated values for ki in the co-current and counter-current cases are 0.034 cm • min" 1 and 0.044 cm • min" 1 , respectively.…”
Section: Mass Transfer Coefficientmentioning
confidence: 99%
“…It is well established that hindered amine light stabilizers (HALSs) are the most efficient photostabilizers for polyolefins1–4 because of their multifunctional activities in the photostabilization mechanisms. These are summarized by Allen and Edge5 as follows: chain‐breaking donor/acceptor redox mechanism through the nitroxyl/substituted‐hydroxylamine intermediates, decomposition of hydroperoxides by the amine during processing, inhibition of the photoreaction of α,β‐unsaturated carbonyl groups in polyolefins, reduction in the quantum yield of hydroperoxide photolysis, singlet‐oxygen quenching (only in polydienes), complexation with hydroperoxides/oxygen, complexation with transition‐metal ions, and excited‐state quenching by the nitroxyl radical. …”
Section: Introductionmentioning
confidence: 99%